Metabolic Action of Metformin - Izabela Szymczak-Pajor; Sylwia Wenclewska; Agnieszka Śliwińska (MDPI AG, 2022)
Metformin, a cheap and safe biguanide derivative, due to its ability to influence metabolism, is widely used as a first-line drug for type 2 diabetes (T2DM) treatment. Therefore, the aim of this review was to present the updated biochemical and molecular effects exerted by the drug. It has been well explored that metformin suppresses hepatic glucose production in both AMPK-independent and AMPK-dependent manners. Substantial scientific evidence also revealed that its action is related to decreased secretion of lipids from intestinal epithelial cells, as well as strengthened oxidation of fatty acids in adipose tissue and muscles. It was recognized that metformin's supra-therapeutic doses suppress mitochondrial respiration in intestinal epithelial cells, whereas its therapeutic doses elevate cellular respiration in the liver. The drug is also suggested to improve systemic insulin sensitivity as a result of alteration in gut microbiota composition, maintenance of intestinal barrier integrity, and alleviation of low-grade inflammation.